2021
DOI: 10.1002/alz.12345
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of proteome profiles in preclinical and symptomatic Alzheimer's disease

Abstract: Proteome profile changes in Alzheimer's disease (AD) brains have been reported. However, it is unclear whether they represent a continuous process, or whether there is a sequential involvement of distinct proteins. To address this question, we used mass spectrometry. We analyzed soluble, dispersible, sodium dodecyl sulfate, and formic acid fractions of neocortex homogenates (mainly Brodmann area 17-19) from 18 pathologically diagnosed preclinical AD, 17 symptomatic AD, and 18 cases without signs of neurodegene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 84 publications
1
15
0
Order By: Relevance
“…SynGOanalysis revealed no enrichment of these proteins towards a specific subsynaptic compartment or biological process. In contrast, a recent proteomics study on the human (pre-clinical) AD cortex revealed changes in proteins related to the secretory pathway and synaptic vesicle endocytosis (e.g., SYT2 and SH3SGL2) [30], supporting the relevance of synaptic homeostasis in AD disease pathology. Proteins related to these pathways were among early responding, late responding and progressively changing protein groups [30].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…SynGOanalysis revealed no enrichment of these proteins towards a specific subsynaptic compartment or biological process. In contrast, a recent proteomics study on the human (pre-clinical) AD cortex revealed changes in proteins related to the secretory pathway and synaptic vesicle endocytosis (e.g., SYT2 and SH3SGL2) [30], supporting the relevance of synaptic homeostasis in AD disease pathology. Proteins related to these pathways were among early responding, late responding and progressively changing protein groups [30].…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, a recent proteomics study on the human (pre-clinical) AD cortex revealed changes in proteins related to the secretory pathway and synaptic vesicle endocytosis (e.g., SYT2 and SH3SGL2) [30], supporting the relevance of synaptic homeostasis in AD disease pathology. Proteins related to these pathways were among early responding, late responding and progressively changing protein groups [30]. In the APP/PS1 mouse model of AD, stronger changes in synaptic vesicle endocytosis proteins have been observed at 3-moa [4,31], suggesting the APP/PS1 model recapitulates especially early synaptic changes induced by Aβ.…”
Section: Discussionmentioning
confidence: 92%
“…At early stages, differentially expressed proteins of the “clathrin-coated endocytic vesicle membrane” (GO: 0030669) and the secretory pathway (R-HSA-432720: “Lysosome Vesicle Biogenesis” and R-HSA-432722: “Golgi-Associated Vesicle Biogenesis”) classes were overrepresented. A comparison of the changes in proteome profile between our neuronal model and the results reported by Li et al, 2021 might help to identify druggable targets for increasing the number of cargoes transported.…”
Section: Discussionmentioning
confidence: 78%
“…Analyses of neuronal immunoprecipitates of α-syn fibrillar assemblies and Aß polymorphs may be useful for identifying the molecular partners interacting directly with these protein assemblies. A recent postmortem proteomics study identified proteins for which abundance changed at different stages of Alzheimer’s disease (Li et al, 2021). At early stages, differentially expressed proteins of the “clathrin-coated endocytic vesicle membrane” (GO: 0030669) and the secretory pathway (R-HSA-432720: “Lysosome Vesicle Biogenesis” and R-HSA-432722: “Golgi-Associated Vesicle Biogenesis”) classes were overrepresented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation